2019
DOI: 10.1007/s00330-019-06234-4
|View full text |Cite
|
Sign up to set email alerts
|

High sensitivity and specificity of 4D-CTA in the detection of cranial arteriovenous shunts

Abstract: PurposeIn a prospective cohort study, we evaluated the diagnostic accuracy of time-resolved CT angiography (4D-CTA) compared to digital subtraction angiography (DSA) for detecting cranial arteriovenous shunts.Material and methodsPatients were enrolled if a DSA had been ordered querying either a dural arteriovenous fistula (dAVF) or a cerebral arteriovenous malformation (bAVM). After enrolment, both a DSA and a 4D-CTA were performed. Both studies were evaluated using a standardized form. If a dAVF or bAVM was f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…However, this invasive technique carries a risk of neurological complications and adverse reactions associated with the contrast agent as well as the exposure to ionizing radiation during the procedure. Various non-or less-invasive imaging techniques have thus been applied to the evaluation of AVS [12][13][14][15][16][17][18][19][20][21][22]. Time-of-flight (TOF)-MRA has been the most widely used of these in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, this invasive technique carries a risk of neurological complications and adverse reactions associated with the contrast agent as well as the exposure to ionizing radiation during the procedure. Various non-or less-invasive imaging techniques have thus been applied to the evaluation of AVS [12][13][14][15][16][17][18][19][20][21][22]. Time-of-flight (TOF)-MRA has been the most widely used of these in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated that 4D-CTA possesses comparable or even superior capabilities to DSA in assessing the main feeding arteries, draining veins, and tumor nest size, with a higher detection rate for microcerebellar AVMs (diameter < 1 cm) compared to DSA ( 53 , 54 ). Furthermore, it exhibits enhanced diagnostic accuracy in detecting cranial arteriovenous shunts ( 55 ). However, given the current technology’s imperfections and the limited scope of related research to small series and case reports, 4D-CTA is currently considered an adjunctive tool to conventional non-invasive diagnostic techniques.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have demonstrated an improvement in the diagnostic accuracy of CTA (3D-CTA and 4D-CTA) techniques for detecting underlying vascular abnormalities [5,9,15,19]. The improvement in 4D-CTA combines the traditional 3D-CTA with the 4th dimension of time to create a stereoscopic image continuously displaying blood vessels within the short interval of time taken for one investigation.…”
Section: Discussionmentioning
confidence: 99%
“…4D- CTA provides a large data set of images and thorough review of all images may help to reduce false-negative cases. For future studies, it would be prudent to assess inter-rater reliability to avoid the introduction of any potential errors that may be producing the observed variability [19]. The level of training for reading 4D-CTA scans should also be standardised across centres to reduce any potential discrepancies, particularly in nonspecialist district general hospitals.…”
Section: Discussionmentioning
confidence: 99%